Vegetative Growth Analysis of Long Beans (Vigna sinensis L.) After Bokashi and NPK Fertilizer Treatment - Raksun, Ahmad; Zulkifli, Lalu; Mertha, I Wayan; Santoso, Didik; Ilhamdi, Moh Liwa (Jurnal Biologi Tropis, 2025)
Long beans (Vigna sinensis L.)  require sufficient nutrients for their growth. To increase nutrients, fertilization needs to be carried out using either chemical fertilizers or organic fertilizers. Bokashi is an organic fertilizer that can be applied to agricultural land. Research on the analysis of vegetative growth of Vigna sinensis L due to bokashi and NPK fertilizer treatments has been conducted with the aim of analyzing the effect of bokashi, NPK fertilizer, and the interaction of the two treatments on the vegetative growth of Vigna sinensis L. In this study, a completely randomized design with 2 factors was used. Long bean  growth parameter including number of leaves, leaf length, leaf width and stem length were analyzed using analysis of variance. The results of the study showed that there was an increase in the number of leaves, stem length and leaf length but there was no increase in leaf width after bokashi treatment. NPK fertilizer treatment can increase all growth parameters, The interaction between bokashi and NPK fertilizer did not have a significant effect on the growth parameters of  Vigna sinensis L. Farmers are recommended to use 16 tons of bokashi for 1 hectare of agricultural land combined with 1.5 g of NPK fertilizer for 1 long bean.